2018
DOI: 10.15847/obsobs12420181300
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the distribution of non-professional subtitles to study new audiences

Abstract: This paper analyzes the consumers in the context of non-professional subtitling (NPS). Using web scraping techniques to collect data about the downloading rate of non-professional subtitles we explore the behavior of consumers. Drawing on the case of the subtitles for House of Cards in Addic7ed.com, a popular multilingual non-professional subtitle distribution website, we describe the consumption of non-professional subtitles and the users' response. After outlining the situation of the international audiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…In other words, fansubbers make every effort to release subtitles for a given program at the earliest opportunity, and to reach an enthusiastic and larger audience. Additionally, two reasons have been ascribed to the popularity of non-professional subtitling; audiences wish to access foreign audiovisual programs within a shorter time period, and they simply dislike dubbing (Orrego-Carmona & Richter, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, fansubbers make every effort to release subtitles for a given program at the earliest opportunity, and to reach an enthusiastic and larger audience. Additionally, two reasons have been ascribed to the popularity of non-professional subtitling; audiences wish to access foreign audiovisual programs within a shorter time period, and they simply dislike dubbing (Orrego-Carmona & Richter, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although the research has gradually shifted from conventional translation types such as dubbing and subtitling to new emerging modalities, including fan translation, very little research has addressed Persian amateur trans-lation in the realm of avt. Most research on non-professional subtitling is derived from a European and East Asian context (for example see Orrego-Carmona & Lee, 2017b). Given the fertile ground offered by this underexplored phenomenon in Iran, this article is intended to shed some light on this unauthorized and non-professional practice in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of speed and access is supported by the findings of Orrego-Carmona and Richter (2018). The study tracked the downloads of subtitles for the third season of House of Cards over a two-week period after the release of the third season, and found that 66.1% of the total downloads (480,298) occurred during the first four days 1 .…”
Section: The Reception Conditionsmentioning
confidence: 84%
“…To apply Chesterman's proposition of functional quality¸ in what follows I will highlight some of the key findings of a series of studies exploring non-professional subtitling (Orrego-Carmona 2011, 2016bPym, Orrego-Carmona, and Torres-Simón 2016;Orrego-Carmona and Richter 2018). By analyzing the production of reception conditions of nonprofessional subtitling, this review will explore the phenomenon from a holistic perspective and provide a new overview of the NPS communities under consideration.…”
Section: Exploring Quality From a Functional Quality Perspectivementioning
confidence: 99%
See 1 more Smart Citation